Green synthesis of polysaccharide stabilized gold nanoparticles: chemo catalytic and room temperature operable vapor sensing application - Tagad, Chandrakant K.; Rajdeo, Kishor S.; Kulkarni, Atul; More, Pooja; Aiyer, Rohini C.; Sabharwal, Sushma G. (RSC Advances, 2014)
A facile, one pot, completely green, and cheap route for the synthesis of gold nanoparticles (AuNPs) has been developed by using locust bean gum (LBG), both as a reducing and a stabilizing agent. Synthesized AuNPs were characterized by UV-vis spectroscopy, TEM, XRD, dynamic light scattering analysis (DLS) and EDAX. A characteristic surface plasmon peak at 537 nm confirmed the formation of AuNPs. Synthesized AuNPs were found to be an efficient catalyst for the reduction of 4-nitrophenol (4-NP) to 4-aminophenol (4-AP). The reaction follows pseudo-first order kinetics with a rate constant of 14.46 X 10(-2) min(-1). Furthermore, the catalytic efficiency of AuNPs for ethanol vapor sensing was investigated by doping AuNPs in a tin oxide (SnO2) matrix synthesized by a single step thermal decomposition method. The AuNPs doped SnO2 sensor showed a fast response (similar to 5 seconds) and excellent ethanol sensing behavior in the range of 10 to 120 ppm at room temperature. A two fold increase in ethanol vapor sensing response was observed with AuNPs doped SnO2 as compared with the pure SnO2 sensor.

Anti-oxidant properties of ficus religiosa L. Bark extract on human keratinocytes - Dixit, Shailesh S.; Kulkarni, Atul; Seo, Hyo Hyun; Gadgil, Jayant; Dingre, Medini; Umar, Ahmad; Moh, Sang Hyun; Parasharami, Varsha A. (Science of Advanced Materials, 2016)
Ficus religiosa (Sacred Fig) is a medicinally important tree, native to the Indian subcontinent. It has been extensively pharmacologically researched species having wide spectrum of medicinal properties. All parts of F. religiosa tree are known to possess important medicinal properties such as anti-oxidant, anti-inflammatory, wound healing and skin diseases etc. However, effects of F. religiosa on skin cells line HaCaT was not studied for its antioxidant properties. In this report we have investigated F. religiosa bark aqueous extract for its antioxidant properties on human keratinocytes (HaCaT) cell line using DPPH, superoxide dismutase 1, superoxide dismutase 2 and catalase assay. We observed that F. religiosa bark aqueous extract efficiently scavenged (80%) DPPH radicals. Superoxide dismutase1 assay of F. religiosa bark aqueous extract effectively scavenged superoxide radicals (O-2(-)) and showed dose dependent activity. Reactive oxygen species were trapped by superoxide dismutase 2 assay of F. religiosa bark aqueous extract and form hydrogen peroxide. Catalase assay results revelled that hydrogen peroxide was further decomposed to give water and oxygen. Thus various anti-oxidant assays of F. religiosa bark aqueous extract indicate that it efficiently reduced the reactive oxygen species in skin cells.
Keywords: Anti-Oxidant; Catalase Assay; DPPH Assay; Ficus religiosa; Keratinocyte HaCaT Cell Line; Moraceae; SOD Assay

Enhanced anti-ageing and wound healing properties of Ficus religiosa L. bark, leaf and aerial root extract in human keratinocytes cell line (HaCaT) - Pandey, Prem; Seo, Hyo Hyun; Kim, Hye-In; Ryu, Seung Hwan; Dingre, Medini; Moh, Sang Hyun; Kulkarni, Atul; Parasharami, Varsha A. (Vegetos, 2020)
<span style="color: rgb(51, 51, 51); font-family: Georgia, Palatino, serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(252, 252, 252);">Plants have played a vital role in curative and preventive healthcare. <i style="box-sizing: inherit; color: rgb(51, 51, 51); font-family: Georgia, Palatino, serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(252, 252, 252);">Ficus religiosa<span style="color: rgb(51, 51, 51); font-family: Georgia, Palatino, serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(252, 252, 252);"> L., a medicinally important tree has been used as a traditional medicine to treat various ailments and skin diseases. However, its skin anti-ageing properties are not yet scientifically evaluated. Here we report the comparison of <i style="box-sizing: inherit; color: rgb(51, 51, 51); font-family: Georgia, Palatino, serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(252, 252, 252);">F. religiosa<span style="color: rgb(51, 51, 51); font-family: Georgia, Palatino, serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(252, 252, 252);"> bark (FRAqB), leaf (FRAqL) and aerial-roots (FRAqAR) extracts for skin anti-ageing and wound healing properties. FRAqB, FRAqL and FRAqAR extracts preparation, cell culture, RNA isolation, real time PCR, astringent activity and wound healing assay were carried out using standard methods. Axio Observer FL-microscope and ImageJ software were used for wound healing assay analysis. The real time PCR study reveals that matrix metalloproteinase-1 (MMP) RNA was downregulated to 75% and 95% for FRAqB and FRAqAR, respectively. For procollagen C-endopeptidase enhancer 1 (PCOLCE), FRAqB and FRAqL enhanced RNA levels by 500% and 300%, respectively. FRAqB and FRAqL increased wound healing area to about 60% and FRAqAR by 50%. All three extracts demonstrated astringent activity which is significant for skin tightening. The study proves that extracts of <i style="box-sizing: inherit; color: rgb(51, 51, 51); font-family: Georgia, Palatino, serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(252, 252, 252);">F. religiosa<span style="color: rgb(51, 51, 51); font-family: Georgia, Palatino, serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(252, 252, 252);"> are prominent candidates for pharmaceutical and cosmetic applications such as skin anti-ageing and wound healing.